Development of appoinment scheduling agent using distributed constraint satisfaction (DisCS) - Mohd. Azmi, Nurulhuda Firdaus; Eri, Zeti Darleena; Ibrahim, Nuzulha Khilwani; Ahmad Rusli, Rozana Diana (Faculty of Computer Science and Information System, 2008)
Scheduling problem (that is assigning resources and t ime points to given tasks) arise in many real-world domains, for example reservation environment. A reservation environment typically refers to a parallel -machine with n jobs available for processing. The processing time of each job has to fit within a giv en time window and with n jobs available for processing. The goal of this research is to develop appointment scheduling agent in reservation environment with implementation of Distributed Constraint Satisfaction (DisCS). The aim of this development is to optimize the reservation schedule towards efficiency schedule. In the other hand, to improve a better operation system level in organization. In this study, several algorithms were produced for different types of appointment policies and constraints. This study follows the Rational Unified Process (RUP) methodology as software development life cycle (SDLC) in the software development process. The design of the system architecture is illustrated using Unified Modeling Language (UML) technique.